Macrophage polarization during Streptococcus agalactiae infection is isolate specific - Janžič, Larisa; Repas, Jernej; Pavlin, Mojca; Zemljić-Jokhadar, Špela; Ihan, Alojz; Kopitar, Andreja Nataša (Frontiers in Microbiology, 2023)
Streptococcus agalactiae (Group B Streptococcus, GBS), a Gram-positive commensal in healthy adults, remains a major cause of neonatal infections, usually manifesting as sepsis, meningitis, or pneumonia. Intrapartum antibiotic prophylaxis has greatly reduced the incidence of early-onset disease. However, given the lack of effective measures to prevent the risk of late-onset disease and invasive infections in immunocompromised individuals, more studies investigating the GBS-associated pathogenesis and the interplay between bacteria and host immune system are needed. Here, we examined the impact of 12 previously genotyped GBS isolates belonging to different serotypes and sequence types on the immune response of THP-1 macrophages. Flow cytometry analysis showed isolate-specific differences in phagocytic uptake, ranging from 10% for isolates of serotype Ib, which possess the virulence factor protein β, to over 70% for isolates of serotype III. Different isolates also induced differential expression of co-stimulatory molecules and scavenger receptors with colonizing isolates inducing higher expression levels of CD80 and CD86 compared to invasive isolates. In addition, real-time measurements of metabolism revealed that macrophages enhanced both glycolysis and mitochondrial respiration after GBS infection, with isolates of serotype III being the most potent activators of glycolysis and glycolytic ATP production. Macrophages also showed differential resistance to GBS-mediated cell cytotoxicity as measured by LDH release and real-time microscopy. The differences were evident both between serotypes and between isolates obtained from different specimens (colonizing or invasive isolates) demonstrating the higher cytotoxicity of vaginal compared with blood isolates. Thus, the data suggest that GBS isolates differ in their potential to become invasive or remain colonizing. In addition, colonizing isolates appear to be more cytotoxic, whereas invasive isolates appear to exploit macrophages to their advantage, avoiding the immune recognition and antibiotics.